Multioutlet Hydrants in Mediterranean Pressurized Irrigation Networks: Operation Problems and Hydraulic Characterization - Iban Balbastre-Peralta (MDPI AG, 2021)
Multioutlet hydrants as joint network infrastructure remain briefly addressed in the literature. Studies have always been limited to the individual treatment of the hydraulic components but not as a whole element. This study presents the main problems in the field of multioutlet hydrants within hydraulic infrastructure for pressure irrigation networks in Mediterranean agriculture. First, a field study with interviews was carried out in 30 water users associations (WUAs) between 2010 and 2018. Following this study, a laboratory test methodology was proposed to characterize this type of hydrant. Subsequently, four laboratory tests were performed on 12 multioutlet hydrants with different and common configurations found in irrigation networks: (i) head losses produced, (ii) global measurement precision in the multioutlet hydrant, (iii) blockage analysis in meters in vertical orientation, and (iv) hydrant behavior in response to hydraulic transients. The tests show that a horizontal configuration of the measuring elements with fewer than ten outlets and a suitable dimensioning of elements improve element maneuverability, instrument metrology, and irrigation emission uniformity. Finally, the importance of adequate design, dimensioning, and maintenance of the multioutlet hydrant devices is evidenced as a key point for the adequate management of collective pressure irrigation networks.